The responses of fatty acid-binding protein and creatine kinase to acute and chronic exercise in junior rowers - Tse, M.; Glatz, J. F. C.; Chan, C.; Renneberg, R. (Research Quarterly for Exercise and Sport, 2003)
The responses of fatty acid-binding protein (FABP) and creatine kinase (CK) were compared in a group of junior rowers during 5 weeks of training. Acute exercise induced a larger increase in FABP (70-362%) than in CK (24-156%). When the chronic effect of exercise was studied, the baseline FABP levels were independent of previous training. However, the baseline CK level was dependent on the training that took place during 1 day before (F = 4.362, p < .01) and on the combined training on the previous 2 days (F = 4.606, p < .005). The present results suggest that FABP and CK could be used to monitor acute exercise and chronic exercise, respectively.